Case Report: The integration of chemoradiotherapy and immunotherapy in a patient with advanced-stage renal squamous cell carcinoma and pulmonary metastases - Yanlin Niu; Shengchao Wang; Xinzhou Deng; Xinzhou Deng; Ming Luo; Ming Luo; Jingjing Chai; Jingjing Chai; Zhiguo Luo; Zhiguo Luo (Frontiers in Immunology)
Renal squamous cell carcinoma (RSCC) is an uncommon malignancy, representing less than 1% of all renal cancers, and is associated with a notably poor prognosis. Surgical intervention is the primary treatment modality for early and intermediate-stage cases; however, the efficacy of combined chemoradiotherapy and immunotherapy in advanced-stage patients remains unclear. In this report, we present a case of RSCC with pulmonary metastases, wherein the patient attained disease remission following a treatment regimen comprising combined chemo-radiotherapy and immunotherapy. The patient demonstrated a progression-free survival (PFS) of 12 months and an overall survival (OS) of 14 months. This case study aims to provide a comprehensive analysis of the treatment approach, potentially serving as a reference for therapeutic strategies in patients with inoperable RSCC.